Sosialisasi Pendampingan Belajar Anak Pada Masa Pandemi Untuk Kelas Rendah Di SDIT Bina Insani Kediri - Erwin Putera Permana; Alfi Laila; Fahmi Imron, Ilmawati; Sri Mujiwati, Endang (Universitas Nusantara PGRI Kediri, 2021)
The purpose of conducting the socialization of children's learning assistance during the pandemic period for the lower classes at SDIT Bina Insani Kediri is to increase the understanding of the guardians of students about children's learning styles, learning characteristics, psychological development of their sons and daughters so that in accompanying students' learning online, the guardians of the students already have the provisions that enough. This community service uses community assistance methods. This method is used in activities that aim to provide information, increase understanding and awareness to the public. The results of the socialization are based on interviews during socialization at zoom and the results of the questionnaire are that the majority of student guardians already understand about online learning, the obstacles that students experience while learning, and are able to accompany their children to study at home because they realize that parents are important players in learning children at home as a substitute for the teacher at school. The purpose of conducting the socialization of children's learning assistance during the pandemic period for the lower classes at SDIT Bina Insani Kediri is to increase the understanding of the guardians of students about children's learning styles, learning characteristics, psychological development of their sons and daughters so that in accompanying students' learning online, the guardians of the students already have the provisions that enough. This community service uses community assistance methods. This method is used in activities that aim to provide information, increase understanding and awareness to the public. The results of the socialization are based on interviews during socialization at zoom and the results of the questionnaire are that the majority of student guardians already understand about online learning, the obstacles that students experience while learning, and are able to accompany their children to study at home because they realize that parents are important players in learning children at home as a substitute for the teacher at school.